Association Between Serum Biochemistry of Leghorn Chickens and Changes in Renal Tissues Induced by High Calcium and High Urea Diets - Al-Ankari, Abdul-Rahman S. (International Journal of Poultry Science, 2006)
An experiment consisted of three groups of hens that were given basal diet only and/or supplemented with either high calcium or high urea was designed to assess the correlation between serum constituents and the severity of damage to the kidney`s tissues. At weeks 6, 12, 18, 24 and 30 of age, six birds from each group were sacrificed, histology of kidney tissues was examined microscopically and the abnormal changes in tissue were recorded to each bird and scored. Collected blood from 6 birds of each group at weeks 6, 12, 18, 24 and 30 of age was used to estimate serum levels of uric acid, phosphorous, magnesium, calcium, urea and creatinine. The outcome of the study revealed that severity score of kidney tissues was positively correlated with serum levels of uric acid (r = 0.992, P< 0.01) and calcium (r = 0.914, P< 0.01) in the group that was fed high calcium diet. It was also correlated with uric acid (r = 0.994, P< 0.01) and calcium (r = 0.881, P< 0.05) in group that was fed high urea diet. However, levels of serum urea, creatinine, phosphorous or manganese were not correlated (p>0.05) with severity score.